PELAKSANAAN PROGRAM PENDIDIKAN MUATAN LOKAL BERORIENTASI KETERAMPILAN DI SMP LAMPUNG - , Yufiarti (Pendidikan Dasar, 2009)
Abstract, Based on the new  curriculum (KTSP) in Indonesia, each level of education has two hours SKS of LCC subject in each semester. The Local Content Curriculum (LCC) is a creative idea that sprang out of the desire to preserve and develop local cultures. That is, to develop basic skills, life skills, prevocational and income-producing skills, as well as to make the students aware of environmental and other community concerns. The main objective of this research is to describe the impelementations of  Local Content  education in terms of skills orientation  at Junior Secondary School in Lampung province. This research  focused on: (1) The distribution of district, (2) the  subject  matters of  local content  education,  (3) the teacher’s availability, (4),  student’s interest,   and   (5) the facilitation that contribute the  program. This research used descriptive method.  Collecting data  used questionnaire that  disseminated   to 36  Junior  Secondary Schools. Based on the above focuses we could surmise that (1) The  programs  was distributed  in some  district, (2) Local content education consisted of  various skills subject matters, (3) Teachers were  availabel, (4) Most  of  students  interested  follow the  programs, (5) the  facilitation  was  enough to contribute the  program.